Effects of pegylated interferon‐α‐2a monotherapy on growth in Japanese children with chronic hepatitis C. Issue 3 (24th April 2013) - Tsunoda, Tomoyuki; Inui, Ayano; Kawamoto, Manari; Sogo, Tsuyoshi; Komatsu, Haruki; Fujisawa, Tomoo
<x xml:space="preserve">Abstract</x> Aim The relationship between pegylated interferon (PEG IFN)‐α‐2a and growth of children with chronic hepatitis C (CHC) remains unclear. This study was to evaluate the effects of PEG IFN‐α‐2a on growth. Methods From 2003–2012, we prospectively analyzed the data of children with CHC through mother‐to‐infant transmission. They were all treatment naive and were treated with PEG IFN‐α‐2a monotherapy. Results Among 31 children (19 boys, 12 girls; median age, 6 years) treated with monotherapy during the study period, 21 children (13 boys, eight girls; median age, 7 years) were statistically analyzed. The median treatment period of the 21 children was 48 weeks (range, 48–72). Z‐scores of height and weight before treatment, at the end of treatment and 1 year after treatment were −0.05, −0.24 and −0.12 (height), and +0.11, −0.23 and −0.05 (weight). Both Z‐scores were significantly decreased at the end of the treatment. One year after treatment, Z‐scores of height and bodyweight were significantly improved compared with that of end of treatment but were still lower than those before treatment, with statistical significance. Z‐scores of height growth velocity was significantly increased after the treatment (+0.71), compared with that during treatment (−2.25). Conclusion PEG IFN‐α‐2a has an inhibitory effect on children's growth, and Z‐scores of height and bodyweight were decreased at the end of treatment. Although Z‐scores improved after the treatment, they had not returned to the baseline level 1 year after the treatment.